THE ORIGINS OF ENGLAND 410-600. - Whittock, Martyn J. ([S.l.])
1 online resource.
Keywords: The Origins of England (1986) gives a comprehensive overview of the crucial period of migration and settlement that can be seen as the beginning of English history. It takes into account recent discoveries and debates on the origins of the English, their arrival and conquest of England, and the social life and culture of the settlers. Topics covered include the resistance of the British to the English invaders, the relation of the English to the crumbling Roman society, the founding of the kingdoms and the Christian missionaries. Besides archaeological evidence, the author considers the evidence of place names, the visual arts and literary and legendary sources.